Analysis Of Demographic, Clinical and Laboratory Profile Among Breast Abscess Patients - Jain, Siddharth; Mahour, Kusum; Jhawar, Riddhi; Garg, Akash; Shree, Mannu (Journal of Neonatal Surgery, 2025)
Background: Breast abscesses are a common clinical condition, primarily affecting lactating women as a result of mastitis. It can also occur in non-lactating women due to a variety of factors such as diabetes, immunosuppression, and trauma. This study evaluates the demographic, clinical and microbiological findings among breast abscess women in a tertiary care hospital. Methods: A total of 100 women diagnosed with breast abscess were divided into two groups. Group A underwent incision and drainage (N=57) and group B underwent needle aspiration (N=43). Demographic data, clinical findings and laboratory profile were extracted from both the groups. Specimens were processed for culture and sensitivity testing. Results: Majority of the women (68.4% in group A and 51.2% in group B) belonged to 21-30 years age group. The common clinical manifestation was breast pain (100%), swelling (100%), fever (66.7% & 76.7%) and tenderness (57% % 100%) in both the groups Majority of the women had primiparous (40.4% in group A and 51.2% in group B) and lactating (78.9% in group A and 95.3% in group B). Staphylococcus aureus was most commonly isolated organism among both the groups (47.4% in group A and 51.2% in group B). Conclusions: Breast abscesses were common in younger lactating women. Pain, swelling, tenderness and fever were the most common clinical findings. Methicillin resistance Staphylococcus aureus was the most common pathogen found in the breast abscess.